Corporate governance in Islamic Banks from an Islamic perspective / Irum Saba and Ahcene Lahsasna - Saba, Irum; Lahsasna, Ahcene (2013)
Purpose - Corporate governance is crucial for the sustainable development of any corporate entity including Islamic banks. Islamic ethics, values and governance should be inbuilt in Islamic banking operations. The purpose of this paper is to discuss corporate governance from the Islamic perspective in relations to Islamic banking with special focus on Malaysia. This paper focuses on the structure of corporate governance, its implementation and relationship with Shariah governance and related parties in Islamic banking by addressing relevant issues and challenges. Design/Methodology/Approach - The paper follows comparative analysis by taking into account the corporate governance, Shariah governance, their relationship and impact on Islamic banking institutions. Findings - The result shows that corporate governance plays a significant role in Islamic banking for image building, goodwill, and performance and there exist a close relationship between Shariah governance and corporate governance for fulfilling the actual objectives of Islamic banking. Practical Implications -This paper is very useful for understanding corporate governance (its framework, practices and relationship with Shariah governance) with a specific focus on Islamic banking institutions. Originality/Value - The paper provides an in-depth knowledge of corporate governance, its importance and models with emphasis on Islamic banks. It adds value by explaining the complementing nature of Shariah governance with corporate governance for better performance and adherence to Shariah in Islamic banks. The nature of challenges and issues in implementation of corporate governance as well as the Shariah governance in IBIs are also discussed in the paper.